Modeling the Binding Mechanism of Remdesivir, Favilavir, and Ribavirin to SARS-CoV-2 RNA-Dependent RNA Polymerase - Byléhn, Fabian (2021)
Recent efforts to repurpose drugs to combat COVID-19 have identified Remdesivir as a candidate. It acts on the RNA-dependent, RNA polymerase (RdRp) of the SARS-CoV-2 virus, a protein complex responsible for mediating replication of the virus's genome. However, its exact action mechanism, and that of other nucleotide analogue inhibitors, is not known. In this study, we examine at the molecular level the interaction of this drug and that of similar nucleotide analogue inhibitors, ribavirin and favilavir, by relying on atomistic molecular simulations and advanced sampling. By analyzing the binding free energies of these different drugs, it is found that all of them bind strongly at the active site. Surprisingly, however, ribavirin and favilavir do not bind the nucleotide on the complementary strand as effectively and seem to act by a different mechanism than remdesivir. Remdesivir exhibits similar binding interactions to the natural base adenine. Moreover, by analyzing remdesivir at downstream positions of the RNA, we also find that, consistent with a "delayed"termination mechanism, additional nucleotides can be incorporated after remdesivir is added, and its highly polar 1′-cyano group induces a set of conformational changes that can affect the normal RdRp complex function. By analyzing the fluctuations of residues that are altered by remdesivir binding, and comparing them to those induced by lethal point mutations, we find a possible secondary mechanism in which remdesivir destabilizes the protein complex and its interactions with the RNA strands.